Improvement of the aroma of lily rice wine by using aroma-producing yeast strain Wickerhamomyces anomalus HN006 - Shoubao Yan (AMB Express, 2019)
Abstract A fruity aroma-producing yeast strain was isolated with the aim of improving the aroma of fermented lily rice wine, and identified as Wickerhamomyces anomalus HN006. In addition, the effects of adding solid residues of previous fermentation cycles, and of fungus α-amylase and W. anomalus HN006 supplementation on the biochemical parameters of lily rice wine were evaluated. The optimum quality of the wine, in terms of ethanol and residual sugar content, acidity levels and aroma, was obtained with 5% (w/v) solid residue addition, and supplementation with 10 U/g fungal α-amylase and 2% (v/v) W. anomalus inoculum on the 4th day of fermentation. Volatile compound profiles, the total amount of amino acids and the sensory characteristics of the lily rice wines produced by the two fermentation processes were also evaluated and compared. The lily rice wine obtained from our optimized experimental technology produced higher amounts of some esters, free fatty acids, alcohols, aldehydes, ketones, alkenes, volatile phenol and thiazole, in addition to higher total amino acid content and sensory scores compared to the traditionally brewed wine. Our process resulted in an intensification and improvement of lily rice wine aroma.